Large-Scale Social Restriction (LSSR) Policy and Dengue Hemorrhagic Fever Cases during the COVID-19 Pandemic in Indonesia: A Case Study of Five Subregions of East Java Province - Trisandy, Aldio Yudha; Maruf, M. Azmi; Yudhastuti, Ririh; Lusno, M. Farid D.; Notobroto, Hari Basuki (UI Scholars Hub, 2021)
The first case of coronavirus disease 2019 (COVID-19) in Indonesia was announced in March 2020. Since then, the number of COVID-19 cases has continued to rise. This prompted the government to adopt Pembatasan Sosial Berskala Besar (PSBB) or large-scale social restrictions (LSSR). Certain areas within dengue fever endemic regions face two challenges: simultaneously tackling COVID-19 and dengue hemorrhagic fever (DHF). Five economic growth centers (a city and four districts) in East Java Province (Gresik, Bangkalan, Surabaya, Sidoarjo, and Lamongan) were affected by the COVID-19 pandemic and adengue fever outbreak. This is a quantitative research with a comparative study design that used the Wilcoxon test to compare cases of DHF pre-COVID-19versus during the COVID-19 pandemic. The Wilcoxon test result showed no significant difference at a p-value of 0.319 (p-value > 0.05). It can be concludedthat DHF still became a challenge in five regions in East Java Province, even though LSSR were implemented. Additional effort is required to tackle DHF. Amethod of preventing and controlling DHF during the COVID-19 pandemic is to build community independence through the